2011
DOI: 10.1097/scs.0b013e3181f76081
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in Fronto-Orbital Advancement

Abstract: Our unit policy in fronto-orbital advancement (FOA) and remodeling has been initial overcorrection to improve the ultimate aesthetic outcome of surgery. To assess relapse of anteroposterior (AP) correction in patients with cranial synostosis undergoing FOA and remodeling, a retrospective pilot study identified patients from the unit database. Serial AP calvarial measurements were used to record surgical and postsurgical changes. Patients showing a change in measurements toward preoperative values were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Indeed, different authors have cited a wide range of complication, reoperation, and recurrence rates. [8][9][10][11][12][13][14] The purpose of this study was to evaluate the complications, revisions, and long-term aesthetic outcomes of patients with isolated metopic synostosis at a single institution.…”
mentioning
confidence: 99%
“…Indeed, different authors have cited a wide range of complication, reoperation, and recurrence rates. [8][9][10][11][12][13][14] The purpose of this study was to evaluate the complications, revisions, and long-term aesthetic outcomes of patients with isolated metopic synostosis at a single institution.…”
mentioning
confidence: 99%
“…Lwin et al reported the relapse of fronto-orbital advancement in an anterior-posterior direction within 5 months postoperatively in 65 % of the analysed patients [23]. In the trigonocephaly group, they reported an operative advancement loss of up to 57 %, which seems very high.…”
Section: Discussionmentioning
confidence: 96%
“…11 Therefore, to solve these problems, the cranial volume should be overcorrected to compensate for postoperative growth suppression to gain enough enlargement at the surgery. 3,12,13 Our distraction approach was 75 mm between the dorsum sellae and the frontal bone on the orbitomeatal plane. 7 This single parametrical criterion is simple and useful for predicting the degree of enlargement of the anterior cranial vault; however, it can be excessive and impractical in early infancy.…”
Section: Discussionmentioning
confidence: 99%